Thalassaemia Management Outcome And Efficiency In Malaysia Siti Rahmah @ Noor Syahireen - Mohammed, Siti Rahmah @ Noor Syahireen (2022)
Thalassaemia is a complex inherited blood disorder requiring life-long medical care. Severe thalassaemia patients require regular blood transfusion and frequent visits to healthcare facilities. Routinely transfused thalassaemia patients necessitate costly iron chelating therapy to prevent iron overload complications that if left untreated, will cause serious morbidity and mortality. Majority of thalassaemia patients in Malaysia rely on public health facilities to receive medical care. Public hospitals providing comprehensive care to thalassaemia patients including routine blood transfusions are termed as thalassaemia care centres (TCC). The high number of transfusion-dependent thalassaemia patients put substantial strain on the healthcare system. Hence, with finite healthcare resources and growing number of patients, policymakers are urgently finding more efficient ways to deliver health services without compromising on quality of care and safety. Thus, the main objective of this thesis is to explore the management and outcome of thalassaemia treatment program in Malaysia. The structure and management of each thalassaemia care centres were characterized by means of qualitative interviews with key opinion leaders as well as by analysing the existing literatures and organizational reports. Next, data envelopment analysis (DEA) was utilized to evaluate the technical efficiency of thalassaemia care centres. Bootstrap truncated regression was then applied to determine the factors affecting the efficiency of thalassaemia care centres.